Pengaruh Penambahan Kombinasi Tepung Sorgum (Sorghum Bicolor L. Moench) dan Tepung Daun Kelor (Moringa Oleifera) terhadap Karakteristik Mie Basah - Mahira Oktaviana, Ni Luh Gede; Kartika Pratiwi, I Desak Putu; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Noodles are an alternative food product made from wheat flour to replace rice. The addition of moringa leaf flour in noodle production is expected to enhance nutritional value while maintaining sensory acceptability. This research aimed to determine the effect of adding a combination of sorghum flour and moringa leaf flour to wet noodles on their attributes and to identify the optimal combination to enhance the characteristics of wet noodles. The experimental method used was a completely randomized design with five combination treatments: 30% sorghum flour with 0% moringa leaf flour, 26% with 4%, 24% with 6%, 22% with 8%, and 20% with 10%. The data were analyzed using analysis of variance (ANOVA), and if significant results were found, the Duncan Multiple Range Test was applied. The results indicated that the addition of a combination of sorghum flour and moringa leaf flour significantly affected (P<0.05) moisture content, ash content, total chlorophyll, crude fiber content, antioxidant activity, color (hedonic test), aroma (scoring test), and overall acceptability. The combination of 22% sorghum flour with 8% moringa leaf flour resulted in the best characteristics of wet noodles, with 63.81% moisture content, 0.71% ash content, 10.24 mg/L total chlorophyll, 2.39% crude fiber content, 13.99% antioxidant activity, and preferred sensory evaluation results in terms of taste, color, aroma, texture, and overall acceptability.